2020
DOI: 10.1177/0003134820979595
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in Patients on Venovenous Extracorporeal Membrane Oxygenation: Is It Safe?

Abstract: Background The anticoagulation and coagulopathy associated with venovenous extracorporeal membrane oxygenation (VV-ECMO) lead to concern for increased risks of tracheostomy. The purpose of this study is to evaluate the safety of tracheostomy in patients on VV-ECMO. Methods Patients admitted between November 2015 and January 2019 to a dedicated intensive care unit for VV-ECMO were reviewed retrospectively. Results 96 patients underwent tracheostomy. Tracheostomy was performed percutaneously in 51 patients, open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 8 , 9 , 17 , 18 However, others have found a significant risk of bleeding, with an incidence of major bleeding between 2% and 11% and minor bleeding between 30% and 40%. 7 , 8 , 19 , 20 Other less frequent complications include ECMO circuit dysfunction, 7 pneumothorax, 19 and loss of airway, 21 among others. Adverse events following tracheostomy were rare in our cohort, the most common being bleeding, echoing the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 17 , 18 However, others have found a significant risk of bleeding, with an incidence of major bleeding between 2% and 11% and minor bleeding between 30% and 40%. 7 , 8 , 19 , 20 Other less frequent complications include ECMO circuit dysfunction, 7 pneumothorax, 19 and loss of airway, 21 among others. Adverse events following tracheostomy were rare in our cohort, the most common being bleeding, echoing the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…23 This rate is higher for patients receiving VV-ECMO and has been reported in 29% of patients. 24 In patients with COVID-19, bleeding has been found to be the most common complication of tracheostomy in a systematic review and meta-analysis of these patients. 10 A similar incidence of bleeding was noted in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to historical rates. 24,25 Additional studies with larger cohorts consisting of both obese and nonobese patients may be necessary to determine any subtle impacts of BMI on outcomes in patients with COVID-19 on VV-ECMO who receive tracheostomies. However, the results of this study did not indicate any association between obesity and either increased bleeding risk or elevated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of a tracheostomy has been associated with reduced sedation, increased rehabilitation, improved communication, and better clinical outcomes in select patients (7)(8)(9)(10)(11). Placement of a tracheostomy in a patient supported by ECMO incurs the additional risk of bleeding related to anticoagulation and ECMO-associated coagulopathy (12,13). A recent analysis of four large-volume ECMO centers demonstrated that tracheostomies are commonly performed in patients supported by ECMO for severe acute respiratory distress syndrome from 2009 to 2017 (14).…”
mentioning
confidence: 99%